1998
DOI: 10.1080/09629359891270
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating activities of a natural α1 ‐acid glycoprotein and its carbohydrate chains attached to the Protein‐Free Polymer

Abstract: Immunomodulating effects of a neoglycoconjugate created on the basis of alpha1-acid glycoprotein (AGP) carbohydrate chains and synthetic protein-free carrier have been investigated. It was demonstrated that this pseudo-AGP suppressed PHA- or anti-CD3 antibody-induced lymphocyte proliferation in a dose-dependent manner. Pseudo-AGP revealed a similar antiproliferative effect as the natural AGP samples. Stimulation of the LPS-induced proinflammatory cytokine production by mononuclear cells treated with both natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…AGP was isolated from the peripheral blood of healthy donors by the method of saline fractionation [5,13]. AGP fractions A, B, and C were obtained by means of affinity chromatography on the column packed with Con A-Sepharose 4B [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AGP was isolated from the peripheral blood of healthy donors by the method of saline fractionation [5,13]. AGP fractions A, B, and C were obtained by means of affinity chromatography on the column packed with Con A-Sepharose 4B [4].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, AGP inhibits the proliferative response of lymphocytes stimulated with T cell mitogens and suppresses IL-2 production [2]. Depending on the ratio between glycoforms, AGP can inhibit or stimulate production of TNF-α and IL-1β [1]. In vivo studies showed that AGP protects experimental animals from lethal shock produced by administration of TNF-α or lipopolysaccharide (LPS) [12].…”
mentioning
confidence: 99%
“…In general, the synthesis of preferential AP reactants after the administration of different inducers of the AP response implies specific functions for each protein, that are suited to meet the demands of the reparation processes after a particular trauma. The biological functions of AGP are related to a number of its activities, such as immunomodulatory effects (Pukhalsky et al, 1998;Hochepied et al, 2003), the ability to bind and transport numerous drugs and many other molecules of endogenous (steroid hormones) and exogenous origin (Fournier et al, 2000). It has also been suggested that the partially protective effect of AGP in different rodent Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…A clearly defined function for AGP remains largely unknown however several studies have demonstrated immunomodulatory properties (Pos et al, 1990, Jorgensen et al, 1998aPukhalsky et al, 1998). Thus alterations in glycosylation in certain pathophysiological states, such as the chronic inflammatory condition rheumatoid arthritis (RA), could be significant in terms of an associated immunomodulatory function.…”
Section: Introductionmentioning
confidence: 99%